Quake - Coupe, Robert (Sydney : Weldon Owen, 2008)
Earth is a restless planet. Movements of huge, rocky plates under the surface can cause the ground to shake in earthquakes. Sometimes quakes are mild tremors, but often they are powerful and dangerous.
Keywords: Earth -- Science -- Survival